Determinación del nicho de mercado en el área textil en la Ciudad de Riobamba - Granda Untuña, David Fabricio (2019)
The purpose of this research project was to determine the market niche in the textile area in the city of Riobamba, well, nowadays the textile industry is one of the companies that have the greatest contribution to the national economy, as clothing They are products of mass consumption and of first necessity. Thus, through the respective investigation in the City of Riobamba and the National University of Chimborazo, it was possible to determine the star products, determine sales volumes and demand projections, data with which the entrepreneur can undertake his future business In the development of the research, the design of the garment designs was proposed using the QFD quality function deployment tool, in which, through the requirements of potential clients, technical specifications developed with an expert in confections and the comparison with competing products, an improved product was developed, selecting different inputs and proposing technical data sheets to maintain quality control at the time of its elaboration, as well as, through research development, He raised the production estimation analysis that should be developed by a company that wishes to enter the textile manufacturing market, this by means of the statistics data on-demand projection in each of the star products determined with the application of the survey.